Spin current and second harmonic generation in non-collinear magnetic systems: the hydrodynamic model. (26th March 2018) - Karashtin, E A; Fraerman, A A
Abstract: We report a theoretical study of the second harmonic generation in a noncollinearly magnetized conductive medium with equilibrium spin current. The hydrodynamic model is used to unravel the mechanism of a novel effect of the double frequency signal generation that is attributed to the spin current. According to our calculations, this second harmonic response appears due to the 'non-adiabatic' spin polarization of the conduction electrons induced by the oscillations in the non-uniform magnetization forced by the electric field of the electromagnetic wave. Together with the linear velocity response this leads to the generation of the double frequency spin current. This spin current is converted to the electric current via the inverse spin Hall effect, and the double-frequency electric current emits the second harmonic radiation. Possible experiment for detection of the new second harmonic effect is proposed.